Video-reportaje sobre los impactos socio-económicos que se han producido por la devaluación del peso colombiano desde la perspectiva de los productores de la ciudad de Tulcán en el periodo 2014-2015 - Córdova Piñaloza, Ligia Magaly (2016)
This paper reports an investigation that the socio-economic impacts in the producers in the city of Tulcán consequence the devaluation of the Colombian peso in the year 2014-2015. In the last year (2014-2015) the dollar appreciation has become more noticeable against the devaluation of the Colombian currency, which generates several obstacles to keep the country economically stable, taking as a quick measure of implementing safeguards solution. This implies that for ecuadorians buy in Colombia find it cheap even with paying taxes and that is why there is a flow of ecuadorians traveling to Ipiales to make purchases, affecting trade directly in the city of Tulcán for lack consumer. As the main contribution of the research is to present information about the process of devaluation of the Colombian peso and the factors that have contributed to unbalance the economy of Tulcán producers who palpate the root problem, so that the reader use as an effective research tool. This document is intended primarily to producers and consumers of the border area of Carchi, in addition to the primary sources of our research, as zonal authorities and experts in the field. Secondly, it is aimed for those passionate about the subject and can use it as a reference guide for similar investigations; and finally, to anyone who can access our work as a source of information.